A Nantucket wedding [compact disc, unabridged] : a novel - Thayer, Nancy, 1943- (Brilliance Audio, Inc., 2018)
It's summer on Nantucket and Alison is finally engaged to the love of her life. Things would be perfect, if only she could make peace between her daughters. Felicity, wild at heart yet a loving mother to her own children, and Jane, the extremely organized and high-earning businesswoman, arrive on the island hoping to get through these next few weeks without ruining their mother's big day. But when Felicity's husband reveals a long-term affair and Jane falls for her soon-to-be step-brother, everyone gets way more drama than they bargained for.